(untitled) (The International Journal for Scientific Research, 2024)
Over the past four decades, particularly in the Arabian Gulf region, there has been a significant increase of non-governmental charitable institutions leading to a wide spread of their humanitarian assistance, social services and diverse construction projects in impoverished and developing countries. Successful implementation of charitable construction projects requires proficient leadership, administrative accumen, and scientific expertise to achieve project objectives in terms of scope, time, cost and quality. This study delves into existing research on extrapolation, utilizating both quantitative and qualitative approaches using digital statistical analysis. By examining all the resolution points and axes, a set of essential criteria has been identified. The criteria can be considered as successful benchmarks for charitable organizations aiming to enhance the implementation of their construction projects.